Applicability of the multistage fitness test in young female soccer players - Castagna, C.; Ditroilo, M.; Bernacchia, B.; D'Ottavio, S. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
The multistage fitness test (MSFT) was proposed as a valid test to assess maximal aerobic power (VO2max) in the general population using a gender and age independent equation (Ramsbottom, Brewer et al. 1988). Nevertheless the MSFT is currently used to assess VO2max in many team-sports including soccer. Despite this, no information are available regarding the predictive accuracy of the Rambottom` formula (Ramsbottom, Brewer et al. 1988) in female young soccer players. Therefore the aims of this study was to examine the accuracy of the original predicting formula in estimating VO2max and the criterion validity of the MSFT in a population of young female soccer players. Twenty-one female soccer players (age 12.1±0.9 years, body mass 50.4±9.2 kg, height 154.9±5.7 cm) with at least three years of experience were randomly chosen among a population of female players (Centro Federale Calcio Femminile, Ancona Italy). After a familiarization session, players were tested over two separate occasions for VO2max (TrackTest) and MSFT performance. Gas analysis were performed during MSFT and TrackTest test with a portable gas analyser (K4b2, COSMED, Rome, Italy). Heart Rates (HR) were recorded using a short-range telemetry system (Polar NV, Kempele, Finland). Results showed that MSFT-VO2max estimation was significantly lower than MSFT-VO2peak (32.72±3.89 vs 40.14±5.92 ml kg-1min-1, p<0.001). No significant difference between TrackTest and MSFT for VO2Peak and HRpeak were observed (38.7±4.7 vs 40.14±5.92 ml kg- 1min-1, and 203±5.3 vs 200±9.8, P>0.05, n=15). Typical error as a CV (TE) were 7.8 (5.9-11.5) and 2.8% (2.2-4.2) for VO2peak and HRpeak comparisons respectively. Estimated MSFT-VO2max vs MSFT VO2peak TE was 7.6% (6.0-10.4). MSFT performance (950±213m) resulted significantly correlated to MSFT-VO2peak (r=0.73, p<0.001). TrackTest-VO2max was not significantly related to MSFT performance (r=0.30, p=0.28). MSFT-VO2peak was significantly related to Estimated VO2max (r=0.70, p<0.01). This study results showed that MSFT formula significantly underestimated VO2peak average difference being in the order of 23% of the estimated value. MSFT-VO2peak resulted significantly related to MSFT performance. Consequently MSFT performance may be considered as an indirect measure of individual VO2max in young female soccer players. Furthermore MSFT may be used as a valid test to assess VO2peak and HRmax when a portable gas analyser and a heart-rate monitor are available. In light of this study results it is suggested to consider MSFT performance (distance covered) and not estimated VO2max when dealing with young female soccer players.